2020
DOI: 10.1080/17482631.2020.1748361
|View full text |Cite
|
Sign up to set email alerts
|

Sharing our story individualized and triadic nurse meetings support couples adjustment to living with deep brain stimulation for Parkinson’s disease

Abstract: Kirkevold (2020) Sharingourstory individualized and triadic nurse meetings support couples adjustment to living with deep brain stimulation for Parkinson's disease,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Access to a multidisciplinary team (e.g., PD nurse, general practitioner, social worker, psychologist, or psychiatrist) gives patients and families increased opportunities and time to discuss psychosocial issues and receive relevant support. Nurse specialists in particular are recommended as they can assist with device practicalities while assisting emotional adjustment (Haahr et al, 2020). They can also provide continuity of care across the patient’s wider illness and treatment trajectory (Eatough & Shaw, 2017; Vann-Ward et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Access to a multidisciplinary team (e.g., PD nurse, general practitioner, social worker, psychologist, or psychiatrist) gives patients and families increased opportunities and time to discuss psychosocial issues and receive relevant support. Nurse specialists in particular are recommended as they can assist with device practicalities while assisting emotional adjustment (Haahr et al, 2020). They can also provide continuity of care across the patient’s wider illness and treatment trajectory (Eatough & Shaw, 2017; Vann-Ward et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, patient characteristics that significantly changed after the psychoeducational program were a decrease in depression at both one and two years after surgery, and a lower anxiety score at one year after surgery [31]. A different study by Haahr et al developed a series of intervention-meetings with a specialized DBS nurse after surgery, resulting in significant improvements in adjusting to life after DBS for both patients and caregivers, as well as adjusting to coping with PD in general [32]. Similarly, a randomized controlled trial conducted in a general PD population showed that a patient-education programme administered to patients and caregivers alike yielded improvements in the domains 'psychosocial problems' and 'need for help' for the caregivers [33].…”
Section: Discussionmentioning
confidence: 99%
“…Through clinical assessment and training, nurses will be able to monitor ADL and instrumental activities of daily living (IADL) of people with PD, to assist them in promoting independence and performance of household tasks. Another common point, cited in studies (17,24) , but, to a lesser extent, was the nurses' ability to instruct people with PD to cope with stress and other psychological demands, as dyskinesias and motor complications can impact the activities or social interactions of people who experience the debilitating effects of the disease.…”
Section: Coordination For the Improvement Of Higher Education Personn...mentioning
confidence: 99%
“…Clinical evidence (13,14,17,18,(21)(22)(23)(24)28,30,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(44)(45)(46)48,50,52) available on self-management education of the disease for people with PD and their care partners involves promoting health for family members and caregivers, providing family education (13,14,24,37,41,44,48,50) and safe sharing space for conversations on sensitive issues ranging from sexual issues of the couple after diagnosis to issues related to palliative care for patients at the end of life (39) .…”
Section: Education For Self-management Of the Disease For People With...mentioning
confidence: 99%